Comparative Analysis of the Various Generalized Ohm's Law Terms in Magnetosheath Turbulence as Observed by Magnetospheric Multiscale. Issue 1 (15th January 2021) - Stawarz, J. E.; Matteini, L.; Parashar, T. N.; Franci, L.; Eastwood, J. P.; Gonzalez, C. A.; Gingell, I. L.; Burch, J. L.; Ergun, R. E.; Ahmadi, N.; Giles, B. L.; Gershman, D. J.; et al.
Abstract: Decomposing the electric field (E ) into the contributions from generalized Ohm's law provides key insight into both nonlinear and dissipative dynamics across the full range of scales within a plasma. Using high‐resolution, multispacecraft measurements of three intervals in Earth's magnetosheath from the Magnetospheric Multiscale mission, the influence of the magnetohydrodynamic, Hall, electron pressure, and electron inertia terms from Ohm's law, as well as the impact of a finite electron mass, on the turbulent E spectrum are examined observationally for the first time. The magnetohydrodynamic, Hall, and electron pressure terms are the dominant contributions to E over the accessible length scales, which extend to scales smaller than the electron gyroradius at the greatest extent, with the Hall and electron pressure terms dominating at sub‐ion scales. The strength of the nonideal electron pressure contribution is stronger than expected from linear kinetic Alfvén waves and a partial antialignment with the Hall electric field is present, linked to the relative importance of electron diamagnetic currents in the turbulence. The relative contribution of linear and nonlinear electric fields scale with the turbulent fluctuation amplitude, with nonlinear contributions playing the dominant role in shaping E for the intervals examined in this study. Overall, the sum of the Ohm's law terms and measured E agree to within ∼20% across the observable scales. These results both confirm general expectations about the behavior of E in turbulent plasmas and highlight features that should be explored further theoretically. Plain Language Summary: Complex turbulent motions are observed in plasmas throughout the Universe and act to transfer energy from large‐scale fluctuations to small‐scale fluctuations, which can be more easily dissipated into the thermal energy of the particles. Electric fields in these plasmas play a central role in enabling the exchange of energy between the magnetic field and the motion of the charged particles and are, therefore, important for disentangling the complex nonlinear dynamics and dissipative processes. Using cutting‐edge, high‐resolution, multispacecraft measurements from NASA's Magnetospheric Multiscale mission, we decompose the electric field in Earth's turbulent magnetosheath into the various terms from generalized Ohm's law, which governs the behavior of the electric field across the wide range of length scales in the plasma. The results confirm a number of general expectations about the relative behavior of the terms in Ohm's law, as well as highlight several new features that are significant for understanding the nonlinear behavior and turbulent dissipation at different scales within the plasma. Key Points: The role of generalized Ohm's law in shaping the turbulent electric field spectrum is examined from magnetohydrodynamic to electron scales The electron pressure term is more significant than expected from linear kinetic Alfvén waves and partially antialigns with the Hall term Relative contributions of linear and nonlinear electric fields are constant with scale and given by average turbulent fluctuation amplitude